STUDENTS' PERCEPTION OF TABLEAU IN EFL CLASSROOM - Aulia Agustin; Susilowaty Susilowaty (LLT Journal: A Journal on Language and Language Teaching, 2019)
This is the qualitative study that examines the students perception of benefits and concerns of tableau used in EFL classroom. Tableau actually is one of the process drama techniques which allows the students to create a living picture using their body, gesture, and facial expression. Tableau is theoretically useful for students to be engaged in reading because it offers all reading strategies. However, there has been few available studies regarding to tableau, especially in EFL classroom context. It was then compelling for conducting the study of how students perceive of their experience in doing tableau in their classroom. The participants were 25 students in one of the EFL classroom in Indonesia. These participants were engaged in doing tableau for three-time meetings. After they experienced doing tableau in their classroom, they were asked to write a reflective journal to know their perceptions in regards to the benefits and concerns of tableau. Moreover, four participants were interview to get deeper understanding of their perception of tableau. The results from reflective journals and interviews revealed that the students perceived several benefits were gained after doing tableau, such as it helps them create sensory images, gain more vocabulary knowledge, deepen characters feeling, learn collaboratively, provide an alternative learning, and creating a fun atmosphere in the classroom. However, they also perceived several concerns about tableau, such as it takes much time, some ineffective groupworks still happens, and they also reported that they found some students misinterpreted the text in tableau.